2001
DOI: 10.1002/1521-3773(20010817)40:16<2954::aid-anie2954>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

In situ IR, NMR, EPR, and UV/Vis Spectroscopy: Tools for New Insight into the Mechanisms of Heterogeneous Catalysis

Abstract: The development of new solid catalysts for use in industrial chemistry has hitherto been based to a large extent upon the empirical testing of a wide range of different materials. In only a few exceptional cases has success been achieved in understanding the overall, usually very complex mechanism of the chemical reaction through the elucidation of individual intermediate aspects of a heterogeneously catalyzed reaction. With the modern approach of combinatorial catalysis it is now possible to prepare and test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(109 citation statements)
references
References 200 publications
(197 reference statements)
0
108
0
1
Order By: Relevance
“…These values are similar to those previously reported in the literature, [47][48][49][50] and a review of the subject has been reported by Hunger and Weitkamp. 56 To understand, the origins of the EPR signal could be assigned to the holes trapped on oxygen atoms, in particular, oxygen vacancies at the particle surface or bulk. Based on our EPR results, we can observe V þ1 O which was discussed previously, and also showed a mixture of V 0 O and V þ2 O for these materials prepared by a microwave-assisted hydrothermal method.…”
Section: -50mentioning
confidence: 99%
“…These values are similar to those previously reported in the literature, [47][48][49][50] and a review of the subject has been reported by Hunger and Weitkamp. 56 To understand, the origins of the EPR signal could be assigned to the holes trapped on oxygen atoms, in particular, oxygen vacancies at the particle surface or bulk. Based on our EPR results, we can observe V þ1 O which was discussed previously, and also showed a mixture of V 0 O and V þ2 O for these materials prepared by a microwave-assisted hydrothermal method.…”
Section: -50mentioning
confidence: 99%
“…In this method, the wavelength of light absorbed by the sample depends on the structure of the sample. With UV-Vis spectroscopy, it is possible to investigate electron transfer between orbitals or bands of atoms, ions and molecules from the ground state to the first excited state [22].…”
Section: Uv-vis Spectroscopic Analysismentioning
confidence: 99%
“…Therefore, the only solution is to adapt spectroscopic techniques in such a way that they are able to monitor catalysts in action"; in other words, to track the physicochemical processes taking place in an active catalyst in real time and under operating conditions. This is the field of in-situ spectroscopy [10,11,[14][15][16][17][18][19][20][21][22][23][24][25]. On the ohter hand, the name operando spectroscopy is gaining popularity in the field because the term defines in a better way the experimental conditions under which spectroscopic data of a catalyst surface should be measured [24].…”
Section: Probing Catalytic Eventsmentioning
confidence: 99%